The comprehensive analysis of pro-environmental food purchasing behaviour among consumers observing halal diet - Mukhtar, D.; Rauf, U.A.A.; Ali, M.H.; Suleiman, N. (Rynnye Lyan Resources, 2024)
This study aimed to analyse the purchasing behaviour of pro-environmental food products among halal-diet consumers by adapting the Theory of Planned Behaviour as a research model. A quantitative method approach involved an online questionnaire administered to Malaysian consumers in Klang Valley to assess their norms, social norms, consumer sustainability orientation and perceived availability towards pro-environmental food consumption. Using structural equation modelling (SEM) in AMOS21, the findings reveal significant (p-value < 0.001) correlations between the Theory of Planned Behaviour constructs towards the environmentally conscious purchase behaviour among halal-dietary consumers. Personal norms, social norms, consumer sustainability orientation and perceived availability significantly influence consumers' environmentally conscious purchases. Therefore, this study contributed to a deeper understanding of pro-environmental food consumption among behaviour halal-dietary observers in Malaysia. Theoretically, there are strong relationships on the pro-environmental behaviour among halal-dietary observers. This study contributed to the existing literature by offering a comprehensive analysis of halal food consumption behaviours among Malaysians, employing quantitative methods within the Theory of Planned Behaviour framework. By examining the interplay between personal norms, social norms, consumer sustainability orientation and perceived availability, this study provided a nuanced understanding of halal food consumption dynamics in the Malaysian context, filling a gap in the literature and offering valuable insights for future research and practical applications. The findings had implications for industry and managers involved in the halal food industry, guiding targeted marketing strategies, product development, and policy initiatives to promote halal food consumption.